ACTION RESEARCH ON MOBILE LEARNING AS A MEDIA TO INCREASE ENGLISH VOCABULARY SKILLS - Kartika; Pradana, Dian Arief; Pambayun , Rizki Nurfida; Afriani, Imroatul Husna (FKIP Unismuh Makassar, 2024)
This study is a classroom action research (CAR) conducted by researchers to improve the quality of learning. This class action research uses mondly as an additional learning media in the classroom to learn vocabulary. Mondly is a language-learning app with a range of engaging features. This study selected Mondly as a tool for classroom learning. The subject of this research is class 12b students at MA N.W school, totaling 20 students. This research using data from pre-test and post-test results as well as observations made by researchers and English teachers to measure student participation and engagement. This study was conducted in a limited time to improve students' scores. The researcher found significant results from the pre-test score of 66.4% and the post-test score of 76.8%, which showed a 10% increase in student vocabulary from the average result. The results of the observation also showed an increase in student activity from 65% to 75%, which showed that students were active in answering questions, and also students collected work sheets on time. It can be concluded that this study has progressed in terms of grades and student engagement between the first and second meetings. Conclusively, Mondly proved to be effective as an additional learning medium due to its engaging features, which kept students motivated and active in class. These findings suggest that integrating Mondly into classroom teaching can have a positive impact on students' learning outcomes in vocabulary.